Codigestão anaeróbia do lodo fresco do flotador e efluente bruto de um abatedouro de aves e potencial da produção de biogás - Araujo , Thays Majara Silva (2021)
The poultry slaughtering and processing industries are generators of large volumes of effluents with high content of organic matter and lipids. These effluents are generated mainly in the physical-chemical treatment stage, which has the purpose of partially removing the organic matter for further biological treatment. Among the possible alternatives, anaerobic digestion provides the transformation of these effluents into biogas, since substrates with these characteristics present high potential for methane generation. The present work aims to evaluate the anaerobic co-digestion of fresh sludge from a flotation unit and raw wastewater (effluent) from a poultry slaughterhouse. In the first stage of the work, an experimental design of the Central Composite Rotational Design (DCCR) type was adopted, comprising a 2² factorial with four tests at levels +1 and -1, four tests at the levels of the axial points (-1.414 and +1.414) and one more triplicate at the central point (0). The response variables were: cumulative CH4 production (L) and CH4 yield (L CH4/g SV added). The reactors were operated in batch under mesophilic conditions (30 ±1 °C), on a laboratory scale with an incubation time of 108 days, testing five levels of fresh sludge from the flotation unit (v/v) (15.9; 20; 30; 40 and 43.5%) and five levels of food/microorganism ratio (A/M) (0.3; 0.5; 1.0; 1.5 and 1.7). In the second stage, an anaerobic sequential batch reactor with immobilized biomass (AnSBBR) was used, operated at mesophilic temperature (30 ±1 °C), for approximately 150 days, during which it was subjected to different applied volumetric organic loads (1.80; 0.9 and 1.57 g/L.d) implemented depending on the variation in influent concentration (3590.14; 2165.39 and 6378.61 mg/L) and cycle time (24, 48 and 24 h), in which the removal of organic matter and the production of methane were evalutated. The efficiency of the anaerobic digestion process was evaluated through the characterization of the influent and effluent, the accumulated production of CH4 and the estimation of the maximum production of CH4, using the modified Gompertz model, considering a confidence interval of 95% (p< 0.05). The results obtained on the effect of fresh sludge dosage and A/M ratio on anaerobic co-digestion did not indicate a significant effect for the response variables: cumulative CH4 yield and cumulative CH4 production. Only the effect of fresh sludge dosage on batch co-digestion showed that the combination of 20% fresh sludge from the flotation unit added to the raw effluent (v/v) was the most favorable for carrying out the anaerobic co-digestion test in the reactor AnSBBR. The best results in the performance of the process in the anaerobic sequential batch reactor with immobilized biomass (AnSBBR) were obtained in condition III, in which a proportion of 20% of fresh sludge from the flotation unit with 80% of raw wastewater was employed. AnSBBR performance indicators also demonstrated operational stability, biogas with 75% methane, volumetric flow of CH4 797.00 mLCH4.d -1 , and removal of 90.43% for total COD and 82.53% for filtered COD. The adjustments in the Gompertz modeling were satisfactory for reactors R1, R7, and R1